Aplikasi Pembekalan Karyawan Baru Di Yomart Menggunakan Training Jarak Jauh - Agung Tri Retnowati (Jurnal Computech & Bisnis (e-Journal), 2017)
Data processing is always a critical task for a company's information systems, so it takes a data processing system that can provide information that has meaning or benefits for the organization itself. Only companies that can use their information effectively can benefit from the opportunity to do things first, faster, more rightly (effectively) and cheaper (efficient) than their competitors. Good information systems should be able to produce quality information that is useful in decision making because the information must be able to reach the interests of management at various levels of management. That for companies needs an application that can help companies in providing training for new employees. This remote training app is useful for new employees as shown with better post test results compared to the previous year.  Keywords: remote training app, new employees.